Eruptive, self-healing melanocytic nevus in a subject with epidermolysis bullosa. - Annicchiarico, G.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
Case report. 12-year-old boy with severe recessive dystrophic epidermolysis bullosa, included in a program of periodic examinations, aimed at monitoring his clinical conditions and precociously diagnosing atypical nevi and malignant tumors. At the age of 8 on the medial surface of the left knee appeared an eruptive nevus, which in a few months covered an 8 cm2 area with irregularly shaped and colored pigmented patches. On dermoscopy, the nevus showed a polymorphous pattern with net, globules and focal hyperpigmentation. Based on previous experience, we diagnosed eruptive melanocytic nevus. The latter was monitored for 2 years remaining practically unchanged. At the age of 12 during a periodic examination we observed the complete regression of the nevus.